2006
DOI: 10.1002/ejsp.388
|View full text |Cite
|
Sign up to set email alerts
|

A study of minorities as victims

Abstract: This article presents the idea that during the 1990s an important change took place in relation between minorities and majorities: the emergence of minorities as victims alongside the formerly predominant active, militant minorities. A hypothesis is raised that these two types of minorities differ in their agenda as well as in the nature of the influence they exert. Active minorities trigger an external conflict with majority and induce conversion (latent rather than overt influence); minorities as victims cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 12 publications
2
45
0
2
Order By: Relevance
“…In line with the approach of social identity theory, vis-à-vis an outgroup protest the support to the protest is neglected when the group is perceived as more threatening. In addition and in line with Moscovici and Pérez's (2007) study on Gypsies, participants declared to be most willing to support the protest when protesters are instead perceived as less threatening. Thus, the common representation of some social groups as threatening or as in opposition to in group's values and culture generally has a great influence on their eventual support.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In line with the approach of social identity theory, vis-à-vis an outgroup protest the support to the protest is neglected when the group is perceived as more threatening. In addition and in line with Moscovici and Pérez's (2007) study on Gypsies, participants declared to be most willing to support the protest when protesters are instead perceived as less threatening. Thus, the common representation of some social groups as threatening or as in opposition to in group's values and culture generally has a great influence on their eventual support.…”
Section: Discussionmentioning
confidence: 58%
“…That is, how much people consider that particular group to be in accordance with the established rules, principles, and values of their society. Moscovici and Pérez (2007) have shown that shared and common representations of minorities affect the way those minorities are approved or disapproved of by the authority and the population. In their study on the representations of Gypsy persecution in Europe, this minority was more likely to be accepted and supported by people when public opinion depicts Gypsies as less threatening.…”
Section: Introductionmentioning
confidence: 99%
“…Similar narratives of victimhood have served to legitimize violence and deflect responsibility for harmdoing in other contexts as well, such as Burundi, Rwanda, and the Congo (Lemarchand, 2009;Mamdani, 2001) or Ex-Yugoslavia (MacDonald, 2002). In other words, the focus on rights resulting from the experience of injustice and victimization appears to be widespread (Passini, 2011; see also Moscovici & Perez, 2007)-even expanding to the perceived right to commit injustice oneself (Bar-Tal et al, 2009).…”
Section: Victim Entitlement In An Age Of Human Rightsmentioning
confidence: 99%
“…This movement seems to imply a clear distribution between duties and rights, according to the social roles in mass violence: while duties to redress and prevent mass violence seem to apply to ''the guilt of nations'' and individual perpetrators (Barkan, 2000), the enhanced focus on rights is now associated with victims (Moscovici & Perez, 2007;Passini, 2011). However, this bifurcation is not necessarily always present.…”
mentioning
confidence: 99%
“…With the move from the perceptual to the social behavioral laboratory, the phenomenon of minority influence and its implications for the conduct of human interaction in the face of conflict -for surely minority influence involves conflict between the haves and the havenots -became clear (Crano & Seyranian, 2007;Moscovici, 1994;Moscovici, Mugny & Pérez, 1985;Moscovici & Pérez, 2007;Mugny & Pérez, 1988). Changing the focus from social influence to persuasion, from perception to attitude, extended the breadth of phenomena that could be studied and created the fertile ground for today's minority influence research (Crano, 2010(Crano, , 2012Crano & Alvaro, 2013Crano & Seyranian, 2007, 2009R.…”
Section: Influence Researchmentioning
confidence: 99%